Phosphorylated xanthan gum, an environment-friendly, efficient inhibitor for mild steel corrosion in aqueous 200 ppm NaCl. (2019) - Vimal Kumar, K.; Appa Rao, B.V.
Abstract: Xanthan gum (XG), a high molecular weight microbial polysaccharide with cellulosic backbone was produced in nature by the bacterium, xanthomonas campestris. XG is enriched with labile hydroxyl groups, which make it a potential molecule as corrosion inhibitor. In the present study an environment-friendly corrosion inhibitor has been developed using chemically modified xanthan gum. Phosphorylated xanthan gum (PXG) has been synthesized by simple addition of phosphate groups on the xanthan gum backbone. By virtue of this chemical modification XG has acquired an increased ability of forming complexes with metal ions mainly with ferrous or ferric ions. The ability of Phosphorylated xanthan gum (PXG) in combating the mild steel corrosion in 200 ppm NaCl corrosive environment was examined using gravimetric studies and electrochemical studies. The morphology of the corroded and inhibited mild steel specimens and the analytical studies of the film formed on mild specimens were carried out using SEM-EDX, XPS and XRD studies. From EIS measurements it was inferred that a maximum inhibition efficiency of about 92.54 % could be achieved in the presence of 150 ppm PXG as inhibitor. Potentiodynamic polarization studies revealed that phosphorylated xanthan gum affects and minimizes both the anodic and cathodic processes of the corrosion of the studied specimens in their respective environments, which means that PXG functions as mixed type inhibitor. More or less identical results were obtained from weight-loss, potentiodynamic polarization studies and EIS studies. Scanning electron microscopic (SEM) studies revealed that in presence of PXG the mild steel surface is less corroded when compared with control. The surface has retained the smoothness when compared with the control. The corresponding EDX spectrum showed the presence of phosphorus peak in presence of inhibitor along with carbon, oxygen and iron peaks. XPS studies inferred that the PXG molecules are the major constituents of the superficial film which was generated on the surface during the course of corrosion inhibition. The present work successfully demonstrated the effectiveness of phosphorylated xanthan gum (PXG) in minimizing the mild steel corrosion in the studied environment of 200 ppm NaCl.